2023
DOI: 10.3390/jcm12031106
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Association of Irritable Bowel Syndrome with Multiple Disease Outcomes: A Phenome-Wide Mendelian Randomization Study

Abstract: Background: This study aimed to identify novel associations between irritable bowel syndrome (IBS) and a broad range of outcomes. Methods: In total, 346,352 white participants in the U.K. Biobank were randomly divided into two halves, in which a genome-wide association study (GWAS) of IBS and a polygenic risk score (PRS) analysis of IBS using GWAS summary statistics were conducted, respectively. A phenome-wide association study (PheWAS) based on the PRS of IBS was performed to identify disease outcomes associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Similarly, in a comparative study in Taiwan including 273 GERD patients, it was discovered that GERD was associated with an increased risk of IBS ( Lei et al, 2019 ). Furthermore, a recent MR study has observed a causal association between GERD and IBS, which supports our findings to a certain extent ( Li et al, 2023 ). However, in their study, patients with IBS had an increased risk of developing GERD, which is inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in a comparative study in Taiwan including 273 GERD patients, it was discovered that GERD was associated with an increased risk of IBS ( Lei et al, 2019 ). Furthermore, a recent MR study has observed a causal association between GERD and IBS, which supports our findings to a certain extent ( Li et al, 2023 ). However, in their study, patients with IBS had an increased risk of developing GERD, which is inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our study utilized both observational and one-sample MR approaches to systematically investigating the causal relationship between COVID-19 and various kidney diseases. While randomized controlled trials are the benchmark for causal inference, MR offers a valuable alternative method that is both time-efficient and cost-effective [ 30 ]. Furthermore, we applied extensive and complementary sensitivity analyses to address potential confounders due to pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a logistic regression model was used to analyze the effect of exposure variables—scaled polygenic risk scores for mild, moderate, and severe COVID-19—against the outcome of COVID-19. This model was adjusted for continuous age, sex (defined as male or female), and the first 10 genetic principal components (continuous variables) [ 30 ]. In the subsequent stage, the scaled predicted exposure values from the first step, which indicate COVID-19 phenotypes, were analyzed for their association with the presence of acute kidney disorder using a Cox proportional hazards regression model.…”
Section: Methodsmentioning
confidence: 99%
“…Although IBS is not a life-threatening syndrome, people with IBS have a reduced quality of life (QoL) [9,10]. The IBS is also closely linked to several psychological comorbidities, such as anxiety and depression, which are the most prominent causes of global disability [11].…”
Section: Introductionmentioning
confidence: 99%
“…The IBS is also closely linked to several psychological comorbidities, such as anxiety and depression, which are the most prominent causes of global disability [11]. In essence, the disorder presents a variety of irritating symptoms, particularly abdominal pain, bloating, constipation, or diarrhea which interfere with patients' lifestyles and result in higher absenteeism and costs, poor productivity, and reduced educational, social, and occupational achievements [5][6][7][8][9][10][11][12]. Patients with IBS utilize more healthcare resources and services than healthy people [11].…”
Section: Introductionmentioning
confidence: 99%